High-expression of LncRNA MAFG-AS1 is associated with the prognostic of patients with colorectal cancer - Cui,Weichun (2020)
SUMMARY OBJECTIVE: Long noncoding RNAs (lncRNAs) have been proven to exhibit distinct functions on the convoluted processes of tumor developments. Some studies on the biological functions of lncRNA MAFG-AS1 (MAFG-AS1) in cancers revealed that they may serve as an oncogene in some kinds of tumors, including colorectal cancer (CRC). However, little is known about the role of MAFG-AS1 in the prognostic of CRC. METHODS: A public dataset was mined for the screening of dysregulated lncRNAs in CRC. Quantitative real-time reverse transcription-polymerase chain reaction(qPCR) was used to compare the levels of MAFG-AS1 between paired MAFG-AS1 specimens and normal adjacent tissues. The correlations between MAFG-AS1 and clinic pathological features in CRC were analyzed using the chi-square test. The log-rank test and Kaplan-Meier test were carried out to compare the survival time of patients with high and low expressions of MAFG-AS1. Cox regression was applied for univariate and multivariate assays to validate whether MAFG-AS1 could be an independent factor in the prognosis of CRC. RESULTS: We found that the distinct upregulation of MAFG-AS1 in various tumors was a common event. MAFG-AS1 was distinctly up-regulated in CRC specimens compared to matched non-tumor specimens (p < 0.01). High MAFG-AS1 expressions were closely associated with depth of invasion (p = 0.011) and TNM stage (p = 0.022). Survival assays revealed that patients with high expression of MAFG-AS1 have a shorter overall survival (p = 0.0030) and disease-free survival (p = 0.0002). CONCLUSIONS: MAFG-AS1 can serve as a novel potential biomarker to predict CRC patients’ survival time.